The influence of the use of the mnemonic method for memorizing the bones of the carpal tunnel by the medical student - EL Marbouh, Abdellah; Daimi, M.; Ammari, M.; Hammani, T.; Tendart, V.; Mounguengui, H.; Khalfaoui, S (International Journal of Scientific Research and Management (IJSRM), 2024)
Anatomy is considered the cornerstone of medical education; Anatomical knowledge is essential for doctors regardless of their specialty. Many articles have compared anatomy teaching methods.This study was designed to evaluate the usefulness of a simple mnemonic method for memorizing the carpal tunnel bones.Twenty-six physiotherapy students, 3rd year trainees in the rehabilitation and functional rehabilitation department, were included in this study,when A majority of students (63.7%) said they were satisfied with the mnemonic method .The influence of using mnemonic method for memorizing the anatomical region studied before or after the course positively influences the students' understanding of anatomy.Based on our experience and student feedback, we strongly advocate the use of the mnemonic method for memorization as a course adjacent in anatomy teaching